2021
DOI: 10.3390/ijerph18010305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Latent Tuberculosis Infection (LTBI) in Patients with Type 2 Diabetes Mellitus (T2DM)

Abstract: Type 2 diabetes mellitus (T2DM) and tuberculosis (TB) together impose a high disease burden in terms of both mortality and health economics worldwide. The objective of this study was to estimate the prevalence and risk factors of latent TB infection (LTBI) in patients with T2DM in Malaysia. A cross-sectional study was performed, and adult T2DM patients (n = 299) were included. Simple and multiple logistic regression analyses were performed to identify the LTBI-associated risk factors in patients with T2DM. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
4
1
1
Order By: Relevance
“…In agreement with our data, which points out an increased prevalence of LTBI among T2D patients ( Table 2 and Figure 2 ), some recent studies also have been reported the association of T2D patients and risk factors of LTBI ( 39 , 40 ). Also, we have observed that T2D patients have produced significant high levels of IFN-γ in response to Mtb-specific antigens from QFT-GIT when compared to non-DM individuals ( Figure 3B ).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our data, which points out an increased prevalence of LTBI among T2D patients ( Table 2 and Figure 2 ), some recent studies also have been reported the association of T2D patients and risk factors of LTBI ( 39 , 40 ). Also, we have observed that T2D patients have produced significant high levels of IFN-γ in response to Mtb-specific antigens from QFT-GIT when compared to non-DM individuals ( Figure 3B ).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding risk factors for tuberculosis, smoking is one of the most well-established, ( 15 ) as well as diabetes. ( 16 ) In our study, neither smoking (p = 0.059) nor diabetes (p = 1.000) were significantly associated with a positive reaction. Since diabetes was only identified through data from medical records, underreported diagnoses might have interfered with this association.…”
Section: Discussioncontrasting
confidence: 74%
“…In 2021, diabetes and its complications will cause 6.7 million deaths worldwide (2). The high mortality was mainly due to cardiovascular disease, kidney disease and infection in T2DM patients (3)(4)(5). People with impaired glucose tolerance have been shown to be at increased risk for the disease (6).…”
Section: Introductionmentioning
confidence: 99%